The Effect of Domestic Violence During Pregnancy on Cortisol Hormone Release, Breastfeeding, and Newborn. Issue 1 (January 2023) - Avcı, Sezer; Ortabag, Tulay; Ulusal, Hasan; Taysi, Seyithan
This study was conducted to determine the effect of domestic violence during pregnancy on the cortisol hormone release, preterm birth, low birth weight, and breastfeeding status. The cross-sectional study was conducted with 255 pregnant women in a Family Health Centre in the Southeastern Anatolia Region of Turkey between October 2017 and August 2018. The questionnaire, DVWDS (Domestic Violence to Women Determination Scale) and Breastfeeding Self-Efficacy Scale were used to collect the data. In the present study, the pregnant women were followed up three times. The first follow-up was applied to the pregnant women in the second trimester, the second follow-up was applied to those in the third trimester, and the third follow-up was applied to the postpartum women. At each follow-up from newborn, cortisol hormone level was taken with saliva and evaluated. It was determined that 9.8% of the pregnant women participating in the study were exposed to violence by their partners. An important result was found that those who were exposed to domestic violence during their pregnancy gave birth in the 37th week ( p < 0.05). It was seen that the babies of those exposed to domestic violence during pregnancy had a higher mean cortisol hormone level ( p < 0.05). It was found that the mean score of the Breastfeeding Self-Efficacy Scale in the third follow-up was lower for those who were exposed to domestic violence during pregnancy than those who were not ( p < 0.05). It was observed during the pregnancy that domestic violence affected cortisol hormone secretion, breastfeeding after birth and newborn health.